Effects of levomilnacipran extended-release on major depressive disorder patients with cognitive impairments: post-hoc analysis of a phase III study - Wesnes, Keith A. (Int Clin Psychopharmacol, 2017)
Performance-based cognitive data were collected using the Cognitive Drug Research System in a study of levomilnacipran extended-release (ER) 40–120 mg/day (NCT01034462) in adults with major depressive disorder. These data were analyzed post-hoc to explore the relationship between cognitive measures, depression symptoms (Montgomery–Åsberg Depression Rating Scale, MADRS), and self-reported psychosocial functioning (Sheehan Disability Scale; SDS). Changes from baseline were analyzed in the intent-to-treat population and subgroups with impaired attention, as indicated by baseline Cognitive Drug Research System scores for Power of Attention and Continuity of Attention. Path analyses evaluated the direct and indirect effects of levomilnacipran ER on SDS total score change. Significantly greater improvements were observed for levomilnacipran ER versus placebo for Power of Attention, Continuity of Attention, MADRS, and SDS score changes; the mean differences were larger in the impaired subgroups than in the overall intent-to-treat population. Path analyses showed that the majority of SDS total score improvement (≥50%) was attributable to an indirect treatment effect through MADRS total score change; some direct effect of levomilnacipran ER on SDS total score improvement was also observed. In adults with major depressive disorder, levomilnacipran ER effectively improved measures of depression and cognition, which contributed toward reductions in self-reported functional impairment.